A retrospective survey of care provided to patients with borderline personality disorder admitted to a female psychiatric intensive care unit. (1st April 2020) - Gintalaite-Bieliauskiene, Kristina; Dixon, Robert; Bennett, Laura
Aims: To survey the characteristics and care pathway of patients with a diagnosis of borderline personality disorder (BPD) admitted to Elizabeth Casson House female PICU over a four year period. To describe the nature of admissions, survey the treatment given, review discharge planning and explore the financial implications of this care. Method: A retrospective descriptive survey of patient records with reference to the standards of care set out by NICE (The National Institute for Health and Care Excellence). Results: Almost a quarter (n = 34, 24%) of patients admitted had a diagnosis of BPD and all had previous contact with mental health services and a complex range of needs. The most common reason for admission in this study was risk of self-harm (n = 34, 74%) and self-harm occurred during the majority of admissions (n = 26, 57%). Intramuscular rapid tranquilisation was used in over a third of admissions (n = 17, 37%). Around a quarter of patients accessed psychological therapies during their admission (n = 8, 28%). The estimated costs associated with these admissions was in excess of a million pounds. Conclusion: This survey suggests striking differences between male and female PICU patients and highlights the challenges of providing evidence based treatment for patients with BPD in a PICU. NICE guidelines recommend the formation of specialist multidisciplinary personality disorder teams which can contribute to reducing episodes of crisis and periods of hospitalisation. The findings of this survey make both a financial and clinical case for this approach to care.